2022
DOI: 10.1109/access.2022.3190798
|View full text |Cite
|
Sign up to set email alerts
|

Applying Combined Action Observation and Motor Imagery to Enhance Classification Performance in a Brain–Computer Interface System for Stroke Patients

Abstract: Motor imagery (MI) and action observation (AO) are mental practices commonly applied in brain-computer interface (BCI) systems for stroke rehabilitation. However, previous studies have reported that combined AO and MI (AOMI) is more effective than MI or AO alone in terms of enhanced eventrelated desynchronization (ERD), which expresses cortical excitability and improves the classification performance of the BCI system in healthy subjects. Nonetheless, evidence the use of this strategy in stroke patients is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Furthermore, the use of video-guided movement during the MI task may boost task attention and guide participants to execute MI more easily, resulting in a significant increase in ERD [14,34]. Moreover, our previous study involving chronic stroke patients revealed that AOMI was superior to MI in terms of enhancing ERD, resulting in improved offline classification performance [34]. Similarly, the classification model in this study was based on ERD features.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Furthermore, the use of video-guided movement during the MI task may boost task attention and guide participants to execute MI more easily, resulting in a significant increase in ERD [14,34]. Moreover, our previous study involving chronic stroke patients revealed that AOMI was superior to MI in terms of enhancing ERD, resulting in improved offline classification performance [34]. Similarly, the classification model in this study was based on ERD features.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, we also found that AOMI-based BCI training was more effective than MI-based BCI training in terms of encouraging the participants to produce more ERD over time. The increased ERD during AOMI-based BCI training may be caused by the automatic activation of the mirror neuron system, which is spontaneously excited by observation of body movement [24,25,33,34]. Furthermore, the use of video-guided movement during the MI task may boost task attention and guide participants to execute MI more easily, resulting in a significant increase in ERD [14,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations